Enhanced recovery after surgery-guided strategies in single-incision laparoscopic totally extraperitoneal hernioplasty for inguinal hernia: a narrative review - Jin, Yi; Zhang, Hongqun; Chen, Yuping; Zhang, Chunyan; Lin, Yan; Wang, Zhuoyin (Frontiers in Surgery, 2025)
ObjectiveTo investigate the clinical efficacy and implementation challenges of single-port laparoscopic total extraperitoneal hernia repair (SIL-TEP) combined with enhanced recovery after surgery (ERAS) in the treatment of inguinal hernia.MethodsThis review summarized the technical advantages of SIL-TEP in reducing postoperative pain, accelerating functional recovery and improving cosmetic results compared with traditional three-port TEP. The perioperative strategies under eras concept were further discussed, including preoperative nutrition optimization, laryngeal mask airway (LMA) use, early oral feeding, multimodal analgesia and timely removal of urinary catheter.ResultsSIL-TEP combined with ERAS had significant clinical benefits, including decreased pain score at 24 h after operation, shortened recovery time of daily activities, and improved patient satisfaction with incision appearance. ERAS interventions have resulted in reduced length of hospital stay; however, there are still technical limitations, including difficulties in device triangulation and learning curve requirements for the number of medical records.ConclusionsThe collaborative application of SIL-TEP and ERAS represents a paradigm shift in minimally invasive hernia management, achieving enhanced recovery metrics and cost-effectiveness. Although the current evidence supports superiority in the short term, more multicenter randomized trials (RCTS) with 5-year follow-up are needed to verify long-term recurrence rates and socioeconomic impact. Standardized training programs and AI-assisted surgical systems may address existing technical barriers to widespread adoption.